PENGARUH DAYA TARIK IKLAN SHOPEE VERSI "12.12 BIRTHDAY SALE 2020" DI MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN MELALUI APLIKASI SHOPEE (Survei Pada Followers Instagram @shopee_id) - Dimas Puguh Irvananda (2021)
This research aims to determine the relationship and the magnitude of the influence appeal of Shopee advertising "12.12 Birthday Sale 2020" in social media Instagram toward Purchasing Decisions through the shopee application. The relevant theory in this research is A-T-R Theory (Awareness, Trial, Reinforcement). This research was conducted using a quantitative research approach. The research method used in this research is the survey method. The population of this research is followers of Shopee indonesia official Instagram account with the number of samples obtained as many as 100 respondents. The technique of analyzing measure the effect of Variable X on Variable Y uses a regression test and the coefficient of determination test. The data testing technique was processed using the SPSS (Statistical Product and Service Solution) version 20 program. The results of this research indicate that the correlation between variable X and variable Y has a very strong relationship. Based on the calculation of the coefficient of determination, it is found that the influence of variable X on variable Y is 65.9%, while the rest can be influenced by other factors outside of the research. The results are supported by the hypothesis test, results that Ho was rejected and Ha accepted which means the influence appeal of Shopee Advertising has an effect on the purchasing decisions